2013
DOI: 10.1111/liv.12033
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin ameliorates high‐fat and high‐cholesterol diet‐induced nonalcoholic steatohepatitis in rats

Abstract: These data suggest that rosuvastatin improved not only hepatic steatosis but also hepatic injury and fibrosis via improved peroxisomal β-oxidation in this rat HFHC model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Simvastatin decreased hepatic inflammation and fibrosis through the inhibition of Ras and RhoA pathway, but without significant changes in steatosis or intrahepatic cholesterol content in a nonalcoholic steatohepatitis (NASH) mouse model [35]. In methionine-choline-deficient diet (MCDD) fed mice, statins have shown to prevent MCDD-induced NASH, restoring mitochondrial and peroxisomal fatty acid oxidation through attenuation of the decreased expression of peroxisomal proliferator-activated receptor α (PPARα) induced by NASH, independent of cholesterol levels [36, 37]. Rosuvastatin decreases free fatty acid liver content in high-fat high-cholesterol diet-induced NASH in rats, and reduces inflammatory markers (TNF-a, IL-6, ALT) and inflammation in histology [37].…”
Section: Pre-clinical Studies Of Statins In Liver Diseasementioning
confidence: 99%
“…Simvastatin decreased hepatic inflammation and fibrosis through the inhibition of Ras and RhoA pathway, but without significant changes in steatosis or intrahepatic cholesterol content in a nonalcoholic steatohepatitis (NASH) mouse model [35]. In methionine-choline-deficient diet (MCDD) fed mice, statins have shown to prevent MCDD-induced NASH, restoring mitochondrial and peroxisomal fatty acid oxidation through attenuation of the decreased expression of peroxisomal proliferator-activated receptor α (PPARα) induced by NASH, independent of cholesterol levels [36, 37]. Rosuvastatin decreases free fatty acid liver content in high-fat high-cholesterol diet-induced NASH in rats, and reduces inflammatory markers (TNF-a, IL-6, ALT) and inflammation in histology [37].…”
Section: Pre-clinical Studies Of Statins In Liver Diseasementioning
confidence: 99%
“…Similarly, in animal studies it has been reported that rosuvastatin ameliorates WD-induced liver steatosis in rats by decreasing TNF-α, IL-6, TGF-β and type-1 pro-collagen expression [40]. The reverse of WD-induced fibrotic NASH in obese, diabetic mice by atorvastatin is believed to be related to inactivation of JNK and reduction of hepatocyte apoptosis and inflammatory recruitment [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some statins increase the adiponectin level, whichmaydecreaseFFAdeliverytotheliverandthus slowtheprogressionofsteatosis 128,139) .Arecentstudy demonstrated that atorvastatin therapy prevents dietinducedlipidaccumulationintheliveringuineapigs via the downregulation of hepatic CD36 proteins, which subsequently facilitates the hepatic uptake of lipids 140) . In a diet-induced fatty liver animal model, rosuvastatin was found to ameliorate hepatic fibrosis in association with a decrease in the hepatic mRNA expressionofTGF-β,connectivetissuegrowthfactor andtype-1procollagen 138) . Therefore,bothinvitroandinvivostudiessuggestthatstatinsplayaprotectiveroleinthedevelopmentandprogressionofNAFLDviavariousmechanisms.…”
Section: Effects Of Statins On Fatty Livermentioning
confidence: 99%
“…Atorvastatin improves the disease activity viaitsTNFα-loweringeffectsinbiopsy-provenNASH patients 137) , and rosuvastatin significantly ameliorates hepatic lobular inflammation by decreasing the hepaticmRNAexpressionofTNFαandIL6 138) . Some statins increase the adiponectin level, whichmaydecreaseFFAdeliverytotheliverandthus slowtheprogressionofsteatosis 128,139) .Arecentstudy demonstrated that atorvastatin therapy prevents dietinducedlipidaccumulationintheliveringuineapigs via the downregulation of hepatic CD36 proteins, which subsequently facilitates the hepatic uptake of lipids 140) .…”
Section: Effects Of Statins On Fatty Livermentioning
confidence: 99%